EDUCATIONAL AND SPIRITUAL ESSENCE OF THE JADIDIST MOVEMENT AND ITS SIGNIFICANCE IN THE MODERN EDUCATIONAL SYSTEM - Tursunboyeva X. S. (Modern American Journals, 2025)
This article explores the educational and spiritual essence of the Jadid movement and its significance in the modern educational system. It analyzes the activities of Jadid enlighteners aimed at establishing new-method schools, introducing advanced pedagogical approaches, and fostering patriotism and humanism among youth. The paper also highlights the compatibility of Jadid ideas on education, social justice, and national awakening with current educational reforms. In conclusion, it emphasizes the importance of studying Jadid heritage in depth and integrating it into the educational process as a key factor in the development of national education.
Keywords: Jadidism, enlightenment, new-method schools, national awakening, educational reforms.